Frailty transitions and types of death in Chinese older adults: a population-based cohort study - Liu ZY (Dove Medical Press, 2018)
Zu-yun Liu,1,* Yin-zhi Wei,2,* Li-qing Wei,3,* Xiao-yan Jiang,4 Xiao-feng Wang,5 Yan Shi,6 Hua Hai7 1Department of Internal Medicine, Yale School of Medicine, New Haven, CT, USA; 2Department of Geriatrics, Huangshi Central Hospital, Edong Healthcare Group, Huangshi, China; 3Department of Medical Laboratory, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China; 4Key Laboratory of Arrhythmias of the Ministry of Education of China, Tongji University School of Medicine, Shanghai, China; 5Unit of Epidemiology, Ministry of Education Key Laboratory of Contemporary Anthropology, School of Life Sciences, Fudan University, Shanghai, China; 6Department of Emergency, Huai’an Second People’s Hospital and the Affiliated Huai’an Hospital of Xuzhou Medical University, Huai’an, China; 7Department of Intensive Care Unit, Xuyi People’s Hospital, Xuyi, China *These authors contributed equally to this work Background: Little is known about the adverse effects of frailty transitions. In this study, we aimed to characterize the transitions between frailty states and examine their associations with the type of death among older adults in China, a developing country with a rapidly growing aging population. Methods: We used data of 11,165 older adults (aged 65–99 years) from the 2002 and 2005 waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS). Overall, 44 health deficits were used to construct frailty index (FI; range: 0–1), which was then categorized into a three-level variable: nonfrail (FI ≤0.10), prefrail (0.10< FI ≤0.21), and frail (FI >0.21). Outcome was four types of death based on bedridden days and suffering state (assessed in the 2008 wave of CLHLS). Results: During the 3-year period, 3,394 (30.4%) participants had transitioned between different frailty states (nonfrail, prefrail, and frail), one-third transitioned to death, and one-third remained in previous frailty states. Transitions to greater frailty (ie, “worsening”) were more common than transitions to lesser frailty (ie, “improvement”). Among four categories of frailty transitions, “worsening” and “remaining frail” had increased risks of painful death, eg, with odds ratios of 1.92 (95% confidence interval [CI] =1.41, 2.62) and 4.75 (95% CI =3.32, 6.80), respectively, for type 4 death (ie, ≥30 bedridden days with suffering before death). Conclusion: This large sample of older adults in China supports that frailty is a dynamic process, characterized by frequent types of transitions. Furthermore, those who remained frail had the highest likelihood of experiencing painful death, which raises concerns about the quality of life in frail populations. Keywords: frailty, transition, older adult, death